One-year outcomes of a conformable single-shot pulsed-field ablation catheter for the treatment of paroxysmal atrial fibrillation - Reddy, Vivek Y; Peichl, Petr; Kautzner, Josef; Anter, Elad; Metzner, Andreas; Koruth, Jacob; Jais, Pierre; Rackauskas, Gediminas; Petru, Jan; Funasako, Moritoshi; Marinskis, Germanas; Turagam, Mohit; et al. (Heart rhythm, 2025)
BACKGROUND: Most single-shot pulsed-field ablation (PFA) catheters require extensive repositioning for pulmonary vein isolation (PVI), posing a challenge for obtaining contiguous, durable lesions. OBJECTIVE: To determine 1-year outcomes of a single-shot, all-in-one mapping and ablation PFA catheter for treating paroxysmal atrial fibrillation (PAF). METHODS: After PVI with the large-lattice catheter with expandable tip (Sphere-360), follow-up included Holter monitoring at 180 and 365 days and scheduled/symptomatic trans-telephonic monitoring (TTM) or modeled insertable loop recorder (ILR) data. Efficacy outcomes were acute PVI and 12-month freedom from atrial arrhythmias (AA), after 90-day blanking. Optional invasive remapping at 75 days facilitated waveform refinement from PULSE1, PULSE2, to the optimized PULSE3. RESULTS: At 3 centers, 100 PAF patients underwent PFA with PULSE1 (n = 30), PULSE2 (n = 20), or PULSE3 (n = 50). Procedure, left atrial dwell, and fluoroscopy times were 57.9 ± 20.6, 22.2 ± 11.8 and 6.8 ± 5.7 minutes, respectively. All 395 targeted PVs were acutely isolated, with a transpired PVI time of 11.5 ± 6.0 minutes, using 4.0 ± 1.3 lesions/PV. There were no primary safety events (serious device-related events within 7 days post-PFA). PVI durability with PULSE3 (n = 40) was 98% (per-vein) and 93% (per-patient). One-year freedom from AA recurrence was 82.0% (95% CI:73.0%-88.3%) overall, and 88.0% (95%CI, 75.2%-94.4%) for PULSE3 patients. Of the ILR sub-cohort (n = 15 PULSE3 patients), 3 patients (20%) had recurrences, with an AA burden reduction from 26% (baseline) to 1.6% (post-ablation). CONCLUSION: The large lattice PFA catheter was efficient, safe, and effective in treating PAF. The observed high PVI durability translated to clinical effectiveness, even in continuously monitored patients.
Keywords: výsledek terapie; Male; Equipment Design; následné studie; Heart Conduction System; Aged; mužské pohlaví; senioři; Catheter Ablation; design vybavení; Follow-Up Studies; Atrial Fibrillation; Treatment Outcome; Pulmonary Veins; Time Factors; lidé; převodní systém srdeční; ženské pohlaví; Humans; Burden; Electrocardiography, Ambulatory; časové faktory; venae pulmonales; Pulsed-field ablation; Atrial fibrillation; elektrokardiografie ambulantní; Female; katetrizační ablace; Catheter ablation; lidé středního věku; Mapping; fibrilace síní; Middle Aged